A PHENOMENOLOGICAL STUDY OF BEAUTY ENTREPRENEURS, THEIRS FINANCIAL COMPETENCE JOURNEY - Virza Alamsyah (Institute of Computer Science (IOCS), 2021)
This study aimed to explain the issues of entrepreneurship and financial competence that exist in Beautypreneurs. This research chooses the qualitative approach using a phenomenological study, which involves in-depth interviews with six Beautypreneurs who are active in building businesses and developing their financial competencies. This phenomenological study is developed based on four main categories, namely are 1. Socio-economic problems, 2. work-life balance, 3. financial knowledge, 4. self-improvement. This study suggests that, firstly, Beautypreneurs have a discursive learning pattern when developing their financial competencies. The second thing, this study found that the personal resilience they try to build based on the cognitive deepening process obtained from the crisis, so these Beautypereneurs needed high mentoring by the mentor who understood the Financial knowledge. Third, they see investation as the best way to develop their financial literacy